2002
DOI: 10.3989/scimar.2002.66s2125
|View full text |Cite
|
Sign up to set email alerts
|

Geographical patterns in abundance and population structure of <i>Nephrops norvegicus</i> and <i>Parapenaeus longirostris</i> (Crustacea: Decapoda) along the European Mediterranean coasts

Abstract: SUMMARY:The main characteristics concerning distribution, size structure and total mortality of two of the most important decapod crustaceans of commercial interest in the Mediterranean Sea, Nephrops norvegicus and Parapenaeus longirostris, are studied along the European Mediterranean coasts. The study is based on data collected during a series of six trawl surveys performed in spring from 1994 to 1999 from the Gibraltar Straits to the Aegean Sea. The population size structure identified in the different geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 28 publications
7
71
0
3
Order By: Relevance
“…Similar results were obtained by Abad et al (2007) in the Alboran Sea (south-western Mediterranean), where rose shrimp was captured by the bottom trawl fleet between 150 and 350 m depth. However, this is not a general rule for the Mediterranean, as standardised experimental MEDITS surveys reported the presence of this species from 50 m depth (Abelló et al, 2002). According to these authors, it is in these shallow waters that juveniles and larvae are usually found, while larger individuals are distributed in deeper waters, which is also reflected in our study by the increase in the mean length with depth.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Similar results were obtained by Abad et al (2007) in the Alboran Sea (south-western Mediterranean), where rose shrimp was captured by the bottom trawl fleet between 150 and 350 m depth. However, this is not a general rule for the Mediterranean, as standardised experimental MEDITS surveys reported the presence of this species from 50 m depth (Abelló et al, 2002). According to these authors, it is in these shallow waters that juveniles and larvae are usually found, while larger individuals are distributed in deeper waters, which is also reflected in our study by the increase in the mean length with depth.…”
Section: Discussionsupporting
confidence: 69%
“…In the Mediterranean, the most abundant information on deep-water rose shrimp comes from the eastern and central basins, where the species is more abundant than in the western basin (Abelló et al, 2002). Thus, in the eastern and central Mediterranean, there is information available on its distribution (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomass obtained in this study (26.40 kg km -2 ) was higher than similar Nephopidae species (Nephrops norvegicus) on the Catalan Sea (18.87 kg km (Ward and Davis 1987). However, the Norway lobster (N. norvegicus) is distributed between 200 and 500 m (Maynou et al 1998;Abelló et al 2002), but the highest yields take place at the 500 m stratum (Fonseca et al 2007). The size of M. binghami in this study is similar to other Nephropidae species (Nephrops norvegicus) caught in Portuguese waters, ranging from 18 to 59 mm CL (Fonseca et al 2007) and in the Catalan Sea (Spain, northwest Mediterranean), ranging from 12 to 58 mm CL (Maynou et al 1998), but smaller than reported of Nephrops andamicus in South Africa, ranging from 47 to 55 mm CL (Berry 1969).…”
Section: Discussionmentioning
confidence: 81%
“…This epibenthic short-lived species is the main target species of a large fishing fleet working in the eastern Atlantic Ocean and is characterised by high rates of growth and mortality (Abelló et al, 2002). The principal fishing grounds are located in the south of Spain and Portugal (Pestana, 1991;Sobrino et al, , 2000, as well as areas off Morocco, Mauritania, Senegal, Guinea Bissau, Gabon and Angola (Cervantes and Goñi, 1986;Cervantes et al, 1991;Sobrino andGarcía, 1991, 1992a,b).…”
Section: Introductionmentioning
confidence: 99%